Soft power and the media management of energy transition: Analysis of the media narrative about the construction of nuclear power plants in Poland - Piotr Żuk (Energy Reports, 2023)
The aim of this article is to describe the potential of soft power as a tool for shaping energy policy and creating social approval for activities that are not subject to a real, open and independent public debate. The article analyses media coverage about nuclear energy in Poland. The analysis is based on empirical material which appeared in selected media from 2015 to 2021 and includes nearly 5,000 media messages. A quantitative analysis of the market value of the produced media coverage about nuclear energy has been performed. The main types of narratives and arguments used to support nuclear energy have been reconstructed. The author emphasises the possibility of using the concept of soft power in the analysis of media coverages, expert statements, political messages and advertising campaigns created in the context of promoting certain technology models and certain energy policy schemes. The soft power analysis is very appropriate in the context of disputes over the desired model of energy policy and shaping public mood in the face of the energy crisis. It makes it possible to expose the agents of the dominant message, the type of arguments used by them, and also to study in what direction energy policy is developed, what social atmosphere is being built towards the energy models promoted by the state, and what social attitudes are shaped towards them under the influence of soft power mechanisms.